Building Resilient Rural Livestock Systems: Capacity Enhancement and Sustainable Growth in Karang Tunggal, East Kalimantan - Dede Aprylasari; Muh. Ichsan Haris; Ari Wibowo; Fandini Meilia Anjani; Cori Qamara; Suhardi Suhardi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The community service program implemented in Karang Tunggal Village, Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan, aims to strengthen breeders' capacity and support sustainable livestock development with the concept of assisted villages. Through a participatory and collaborative approach, this program involved ten livestock groups and twelve representatives from village officials, GAPoktan, field extension officers, sub-district officials, and the Agriculture and Livestock Service of Kutai Kartanegara district, with a total of 72 participants. The main activities include identifying needs, training, workshops, and discussions regarding sustainable livestock practices. The main focus of this program is the development of livestock areas, feed management, optimization of livestock production and reproduction, application of appropriate technology, and strategies to increase the competitiveness of livestock products. The results of this program show significant improvements in farmers' technical skills, feed stability through planting superior grasses and reduced dependence on commercial feeds. This program increases livestock productivity and income and encourages more sustainable and competitive livestock practices. These findings make Karang Tunggal Village a potential model for sustainable livestock development in East Kalimantan.